PLANT GROWTH STIMULATION BvLIGNITE HuMICAcios. PART-I. EFFECT OF AMMONIUM HUMATE ON THE GRO\VTH OF WHEAT - Mira, Surriaya; Abbasiaand, Y Z; Khanb, A Rasheed (Biological Sciences - PJSIR, 2002)
) Humicacids were prepared by nitric acid oxidation of Lakhracoal. The product was alkali soluble polymeric material having an aromatic characteristic. Ammonium salt of the h umicsubstances was prepared to find out itseffects in the presence and absence of N-fertilizer on the yield of wheat, biological yield of whole plant and number of tillers associated with the plants. The addition of ammonia salt of humicacids increased the size of grain, plant and leaves. The small dose of 0.5 kgha·1alone and in combination with half dose of N-fertilizer (60 kg ha·1is the optimum dose of growth stimulationof wheat in Sindh. It suggests that the agricultural soil of experimental site is rich in humousmaterial.